Design and Implementation of Health Supplies Inventory Monitoring System Using First Expired First Out Method - Sri Wulandari Samsul; Harlinda L; Sugiarti (Indonesian Journal of Data and Science, 2023)
The manual management of health supplies inventory by pharmacists at UPTD Puskesmas Toari, Southeast Sulawesi, poses a challenge in monitoring the stock of health supplies due to the manual recording, resulting in less effective monitoring of the inventory. This study aims to design a monitoring system for health supplies inventory using the First Expired First Out (FEFO) method. The FEFO method is suitable for managing the dispensing of health supplies that are closest to their expiration date by utilizing them first to avoid any expired supplies being consumed. The development of this health supplies inventory monitoring system will utilize the waterfall method, consisting of five stages: Requirement Analysis, Design, Implementation, Testing, and Maintenance. The system will be web-based, providing efficient management of health supplies inventory, including medications, disposable medical materials (BMHP), and medical equipment, while also providing timely and accurate information. The research findings indicate that the system can effectively monitor the health supplies inventory at the UPTD Puskesmas Toari Pharmacy Warehouse, utilizing the FEFO method to prioritize the dispensing of health supplies with the nearest expiration date. The system also includes a notification feature to inform the need for immediate dispensing of health supplies. Questionnaire results showed that respondents agreed with the implementation of the monitoring system at the UPTD Puskesmas Toari Pharmacy Warehouse